SPECIAL FEATURES OF GERMAN ADVERTISING TEXTS AND MODERN APPROACHES TO THEIR STUDY - Vasylchuk, Lyudmila (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article defines the main modern approaches to studying special features in modern German advertising texts. ___________References• Golodnov, A. V. «Lingvopragmaticheskie osobennosti persuazivnoj kommunikacii (na primere sovremennoj nemeckojazychnoj reklamy).» Avtoref. dis. kand. filol. nauk, SPbGU, 2003.• Koltysheva, E. Ju. «Manipuljativnoe vozdejstvie v sovremennom reklamnom tekste (na materiale anglojazychnyh gljancevyh zhurnalov dlja zhenshhin).» Avtoref. dis. kand. filol. nauk, Jaroslavl', 2008.• Meljuhin, I. S. Informacionnoe obshhestvo: istoki, problemy, tendencii razvitija (Moskva, MGU, 1999), 208.• Prusakova, T. P. «Reklama v sovremennoj Rossii (jesteticheskij analiz).» (Diss. kand. filos. nauk, Moskva, 2000), 144.• Boos, L. «Grau oder großartig? Die kommerzielle Inszenierung von Alter: Altersbilder und Identifikationsangebote. Eine empirische Fallstudie zu Alterskonzepten in der strategischen Kommunikation» (Hausarbeit zur Erlangung des Grades eines Dr. Phil. der Philosophischen Fakultät der Westfälischen Wilhelms-Universität Münster, Westfalen, Münster, 2008), 308.• Dyer, G. Advertising as Communication (London, 1995), 288.• Mockelmann, J., Zander, S. Form und Funktion der Werbeslogans. Untersuchung der Sprache und werbepsychologischen Methoden in den Slogans (Goppingen: Kiimmerle 1970), 107.• Römer, R. Die Sprache der Anzeigenwerbung (Düsseldorf: Pädagogischer Verlag Schwann, 1980), 288.
Keywords: advertising, media linguistics, German advertising texts